Application of neutron grating interferometry and tomography to the nineteenth century Korean copper coins - Youngju Kim; M. Cyrus Daugherty; Daniel S. Hussey; Jacob M. LaManna; David L. Jacobson; Jongyul Kim; Caitlyn M. Wolf; Paul A. Kienzle; Daeseung Kim; Minsu Han; Hahn Choo; Seung Wook Lee; et al. (Scientific Reports)
Abstract Distinguishing differences between authentic artifacts and replicas is a significant challenge in the field of cultural heritage. In this study, we explore the application of neutron grating interferometry and tomography techniques to identify Korean copper coins in the nineteenth century of Joseon period by investigating structural differences between genuine objects and replicas. Neutron grating interferometry provides the microstructural information of coins, including features such as pores and precipitates, through a dark field image derived from small-angle neutron scattering. Additionally, neutron transmission tomography examines the three-dimensional internal structures and potentially hidden features of coins. Both neutron imaging techniques highlight regions that contain lead precipitates in the copper alloy, showing consistent agreement with optical imaging and with the quantitative lead content measured by energy dispersive X-ray spectroscopy. The distinct corrosion patterns observed in the authentic coin and replica provide empirical explanations for the general corrosion mechanism of copper alloy. This interpretation finds support in the moderate contribution of dark field contrast from cuprite, which underlies the signal of lead precipitates.